Penerapan Sertifikat Laik Fungsi Bangunan Gedung di Kecamatan Pangkalan Kerinci, Kabupaten Pelalawan - Yalid Yalid; Birman Simamora (Penerbit Goodwood, 2022)
Purpose: This study to explain the implementation of the liability of the application of the liability of the certificate of fitness for the functions of buildings based on Law No. 28 of 2002 on buildings in Pangkalan Kerincsi District, Pelalawan regency. Method: This study is a sociological legal research with empirical approach. Result: The application of the certificate of eligibility for building functions based on Law No.28 of 2002 on building in Pangkalan Kerinci District Pelalawan regency did not run effectively due to: first, the implementation resources in other words lack of experts. Secondly, the facilities that support its enforcement do not yet exist. Third, the lack of public awareness. Constraints on the implementation of the certificate of eligibility for building functions based on Law No. 28 year 2002 about buildings in the District of Pangkalan Kerinci Pelalawan author caused because: first, because of the lack of seriousness of the government. Second, the implementation resources have not been adequate in other words the shortage of experts. Third, the enforcement facility does not yet exist. Fourth, public awareness is still not maximized. Fifth, the public does not understand and understand the importance of building function certificate. Limitations: This study only occurred in the Pelalawan regency of Riau province. Contribution: This research is expected to be useful for the Pelalawan Government, especially related agencies and all people who need knowledge or information about the application of building function certificates.